Regulatory Focus, Motivation, and Their Relationship With Creativity Among Adolescents - Wang, Ling; Cui, Yue; Wang, Xinjing; Wang, Jin; Du, Kaiye; Luo, Zheng (Frontiers in Psychology, 2021)
Due to the close relationship among intrinsic/extrinsic motivation, regulatory focus, and creativity revealed by previous literature, intrinsic/extrinsic motivation may play a mediating role between regulatory focus and creativity. Therefore, the present study aimed to investigate the relationship between regulatory focus and creativity by combining intrinsic/extrinsic motivation. In this study, senior high school students (n = 418) completed the Regulatory Focus Questionnaire, the Working Preference Inventory, the Williams Creativity Assessment Packet, and the Kirton Adaption–Innovation Inventory. The correlation analysis showed that both promotion and prevention focus positively correlated with intrinsic motivation; intrinsic motivation and promotion focus positively correlated with creativity personality and innovative-adaptive cognitive style; and extrinsic motivation and prevention focus negatively correlated with innovative–adaptive cognitive style. Furthermore, a path model showed that promotion focus positively predicted creativity through the mediation of intrinsic motivation. In general, our study suggests that intrinsic motivation plays a mediating role between promotion focus and creativity. Our results complement those of previous studies and serve as inspiration for the cultivation of creativity in classroom or enterprise settings.